Kajian Perancangan, Pelaksanaan, dan Refleksi Pembelajaran Sesuai Kurikulum Merdeka: Calon Guru Profesional di Sekolah Menengah Kejuruan - zawawi, irwani; susanti, dewi; widuri, kinanti kusuma (Universitas Muhammadiyah Gresik, 2024)
The implementation of the Independent Curriculum in Indonesia has attracted significant interest and research in the field of education. The Independent Curriculum which aims to provide independent and flexible learning has been the subject of various studies that focus on its implementation, impact, and relevance in the education system. In the implementation of Lesson Study also uses other approaches, one approach that can be done by implementing the capacity and needs of student interests is using the TaRL (Teaching at The Right Level) approach. This study has a problem formulation about the study of the ability of prospective professional teachers in implementing lesson study with the Teaching at The Right Level (TaRL) approach at the vocational high school level. The purpose of this study is to explore the ability of prospective professional teachers in designing, implementing and reflecting on the learning carried out. This study uses a descriptive method because the researcher is analyzing the problems that are occurring in learning, while the approach uses a qualitative approach. A qualitative research approach is an approach that does not use a statistical work basis, but is based on qualitative evidence. In this study, the researcher found that the ability of prospective vocational high school teachers in designing learning was in the good category, as well as the ability of prospective teachers in implementing learning was in the good category. This is supported by the finding that the ability of prospective teachers is not yet optimal when designing LKPD, learning media, and teaching materials that are integrated/synchronous in learning. In addition, the ability to design LKPD that brings up numeracy literacy as part of the motivation to carry out student-centered mathematics learning has not been seen